Perceraian Perlindungan Hukum Terhadap Hak-Hak Anak Dalam Kasus Perceraian Di Kota Semarang: Perlindungan Hukum Terhadap Hak-Hak Anak Dalam Kasus Perceraian Di Kota Semarang - sevia saputri (CV Rewang Rencang, 2024)
ABSTRACTMarriage often occurs and disputes can lead to a marriage becoming untenable,resulting in divorce. A marriage that ends in divorce will have legal consequencesfor both spouses and the children born from the lawful marriage. This studyexamines Legal Protection of Children's Rights in Divorce Cases in Semarang Cityusing a normative juridical approach. The findings show the need for strengtheninglaws and regulations, as well as public education programs regarding children'srights. The challenges faced include a lack of public education and complicatedbureaucratic procedures. Therefore, improvements in laws, education, andsimplification of procedures are crucial to protect children's rights after divorce.Keywords: Divorce, Protection, Children, Indonesian Law, Court